ANALISIS MODEL PROPAGASI RAY TRACING (BELLHOP) DI PERAIRAN LAUT NATUNA UTARA - Agustinus Agustinus; Henry Munandar Manik; Nawanto Budi Sukoco (Universitas Mataram, 2024)
The waters of the North Natuna Sea are one of Indonesia's areas prone to conflict and traversed by foreign vessels due to their direct bordering with several neighboring countries, demanding effective maritime security assurances. To ensure this security, careful maritime control and monitoring are necessary, especially through the use of monitoring tools such as SONAR to detect foreign objects traversing or entering the waters of the North Natuna Sea. This research aims to analyze the characteristics of underwater acoustic wave propagation patterns, particularly in forming shadow zones, using the Bellhop method. Simulations of the Ray Tracing propagation model (Bellhop) were conducted using the AcTUP v2.2L Toolbox. Temperature and salinity data against depth obtained from Marine Copernicus over one year were used in this research, from January 1, 2023, to December 31, 2023, during both the west and east monsoon seasons. Sound propagation speed calculations were based on the Medwin empirical equation, with a focus on a source depth of 10 meters at frequencies of 100 Hz and 1000 Hz in the North Natuna Sea. The simulation results indicate that during the west monsoon season, underwater acoustic wave propagation patterns reach further distances and decline towards the seabed compared to the east monsoon season. The shadow zone is therefore wider during the east monsoon season. Additionally, the transmission loss values at 100 Hz are almost the same in each season, whereas at 1000 Hz, the transmission loss is higher during the west monsoon season, ranging from 40 dB to 75 dB, compared to the east monsoon season, which ranges from 40 dB to 65 dB.